A study of impacts, threats and solutions for urbanization causing environmental degradation and sustainability - Lasitha. K , Dr. Arul Sheeba Rani (Drugs and Cell Therapies in Hematology, 2021)
Trees being the earth’s lungs can mitigate the current environmental degradation issues. Despite the lack of knowledge on trees, selection criteria with respect to environment, habitat, etc., urban greening and its design program will enhance and complement the critical mediums working on carbon sequestration along with gracious or picturesque visual appeal and beauty of the landscape in urban planning. This indispensable component being responsible for better air quality management is being surveyed in this present study. This design is believed to be highly contributing and replicable in any tropical climates which in turn highly combating global temperature rise, bad air quality, shrinking forest and environmental exploitation. There being no plantation design guides in particular to trees that are environmentally potent, only partial studies were found against environmental degradation studies. Proposed landscape digital design is believed not only to be efficient and helping mastering architects to carefully choose the right trees that are useful in the future for cities that naturally and socio-environmentally friendly way, but also contribute to many aesthetic urban societies.